COMMUNITY PERSPECTIVE ON THE WASTE MANAGEMENT SYSTEM IN LAMBANGSARI BEKASI VILLAGE BASED ON SMART GARBAGE ROBOTS - Yuliarman Saragih; Rahmat Hidayat; Ridwan Satrio Hadikusuma (LPPM Institut Pendidikan Nusantara Global, 2023)
Garbage is an unavoidable part of everyday life. Everyone has to take out the trash. Therefore, waste is a major source of problems that directly affect the environment. Moreover, waste management in Indonesia is definitely not good. Most of the waste is thrown away without being sorted. This also ultimately contributes to the complexity of the waste problem. This research was conducted to determine the perception of the waste management system in the village of Lambangsari Bekasi by utilizing intelligent robots based on IoT (Internet of Things). The survey method used is an online questionnaire filled out by 100 people from the age range of 20-25 years. Respondents consist of students, students to workers. The collected data were analyzed using descriptive statistical analysis techniques. The results obtained from the analysis data are that most of the waste management in Indonesia is not appropriate because of the very low knowledge of understanding waste management by utilizing the latest technology, one of which is IoT-based intelligent robots. In addition, the government also does not educate the public about the importance of sorting waste by type and also does not socialize the movement to dispose of waste.